PEMBUATAN PART RING RAINFORCEMENT MENGGUNAKAN MESIN PRESS STAMPING CHIN FONG 110 - Prasetyo, Dwi; Jannati , Eidelweis Dewi (SEMINAR TEKNOLOGI MAJALENGKA (STIMA), 2023)
PT. Persada Selaras Indonesia is a company engaged in sheet metal stamping and dies in Majalengka Regency. One of the products produced at PT. Persada Selaras Indonesia is Part Ring Rainforcement. In the process of making Part Ring Rainforcement using SPCC-SD material using a CHIN FONG Press Stamping Machine with a capacity of 110 Tons through the process of selecting Dies for the Blanking, Bending, Pierching, Marking, Embosh processes.The researcher used the observation method to find out the Part Ring Rainforcement process, Part Ring Rainforcement, one of the components contained in the vehicle tank which is produced at PT. Persada Selaras Indonesia. The Rainforcement Ring Part Making Process is divided into several parts, namely the Planing process, Blanking Process, Bending + Pierching Process, Marking + Embosh Process, and Quality Control Process.